ANALISIS KEBUTUHAN MEDIA E-APE DALAM PEMBELAJARAN BAHASA BAGI ANAK USIA DINI DI RA AN-NUR TULAKAN JEPARA - Elok Khafidhoh Elok; Irfa’i Fatkhurrohman; Wawan Shokib Rondli (LPSDI Bina Patria, 2023)
Language learning is very important to instill from an early age, because language is an important means of communication. In supporting language development, electromic educational game tools/E-APE are needed to stimulate early childhood language development. Not all schools have E-APE media that are appropriate to the child's ratio, age, and development, so that children feel bored in participating in the learning process. In addition to E-APE media, learning centers that are still teacher-centered are also one of the causes of child boredom. This study used a qualitative design with principals and teachers as key informants as a complement. The results of the study concluded: 1) the learning model used at RA An-Nur Tulakan Jepara uses a group learning model; 2) learning is still centered on the teacher so that children's involvement is not maximized; 3) the use of APE in creating language learning is still in the less category.